Exploring men's and women's experiences of depression and engagement with health professionals: more similarities than differences? A qualitative interview study - Emslie, C; Ridge, D; Ziebland, S; Hunt, K (BioMed Central, 2007)
Background: It is argued that the ways in which women express emotional distress mean that they are more likely to be diagnosed with depression, while men's relative lack of articulacy means their depression is hidden. This may have consequences for communicating with health professionals. The purpose of this analysis was to explore how men and women with depression articulate their emotional distress, and examine whether there are gender differences or similarities in the strategies that respondents found useful when engaging with health professionals. Methods: In-depth qualitative interviews with 22 women and 16 men in the UK who identified themselves as having had depression, recruited through general practitioners, psychiatrists and support groups. Results: We found gender similarities and gender differences in our sample. Both men and women found it difficult to recognise and articulate mental health problems and this had consequences for their ability to communicate with health professionals. Key gender differences noted were that men tended to value skills which helped them to talk while women valued listening skills in health professionals, and that men emphasised the importance of getting practical results from talking therapies in their narratives, as opposed to other forms of therapy which they conceptualised as 'just talking'. We also found diversity among women and among men; some respondents valued a close personal relationship with health professionals, while others felt that this personal relationship was a barrier to communication and preferred 'talking to a stranger'. Conclusion: Our findings suggest that there is not a straightforward relationship between gender and engagement with health professionals for people with depression. Health professionals need to be sensitive to patients who have difficulties in expressing emotional distress and critical of gender stereotypes which suggest that women invariably find it easy to express emotional distress and men invariably find it difficult. In addition it is important to recognise that, for a minority of patients, a personal relationship with health professionals can act as a barrier to the disclosure of emotional distress.